Increasing the Societal Impact of Science, Technology, Engineering, and Math with General Collective Intelligence - Williams, Andy (My University, 2022)
This paper explores how a technique called Human-Centric Functional Modeling (HCFM) might be used to radically increase the societal impact of STEM through a kind of biomimicry. HCFM represents systems in terms of functional state spaces, which enables it to be seen that nature has already solved problems that can be represented in these abstract spaces as being relevant to a wide range of science and engineering disciplines. Namely the same general problem of achieving adaptive general problem-solving ability in any domain can be represented as one that had to be solved by nature's equivalent to engineering and research processes in order for organisms to solve the problem of adapting to any aspect of their environments. This solution can be represented as having been used by nature to address complex problems of adaptation, the equivalent of “wicked problems” in human societies from poverty to climate change. Where these complex problems pose existential challenges, nature has not only solved them but has demonstrated the solutions to have worked for hundreds of millions of years. This paper describes how specific patterns in the use of HCFM and General Collective Intelligence (GCI) might be used to approach each of a range of engineering disciplines as well as a range of sciences and potentially mathematics, in order to create the potential to exponentially increase the societal impact of research and engineering activities.
Keywords: education; General Collective Intelligence; SDGs; STEM; systems engineering; systems thinking